Comparing State-level policy responses to economic reforms in India - Loraine Kennedy; Kim Robin; Diego Zamuner (Revue de la Régulation)
By rewriting the rules of economic governance in India’s federal democracy, economic reforms adopted in the 1990s have had far-reaching consequences on the relations between the Union (or central state) and the States. First, the dismantling of the centralised management of the economy has created greater scope for State governments to elaborate their economic development policies. Second, the reforms require cooperation from State governments and hence State-level politics and governance have taken on greater importance for India’s overall development trajectory. On the basis of fieldwork-based research, this paper discusses policy frameworks in four States (Andhra Pradesh, Haryana, Kerala and Orissa) comparing and contrasting their promotional policies, aimed at attracting investments, as well as their approaches to structural reforms. For each case we explain political actions and discourse using a qualitative political economy approach. The article addresses a gap in the existing literature, which tends to focus on inter-State comparisons of economic performance. There has been relatively little academic attention to the comparative study of State-level policy response to the national economic reform agenda. One of the objectives of this study is to understand how subnational political elites, who now have more ‘policy space’ (if not necessarily more fiscal space), elaborate their economic development strategies in relation to the central state, on one hand, and to social forces in their political jurisdictions, on the other. We examine the social compromises that are expressed by these State-level policies, which provide evidence of the distinct political economies prevailing in India at the subnational level.